Wake up! hip-hop Christianity and the Black church - Kirk-Duggan, Cheryl A.; Hall, Marlon; ebrary, Inc. (Nashville : Abingdon Press, 2011)
"Once seen as only advocating violence, Hip Hop can be the church's agent of salvation and praise to transform society. After looking at Hip Hop's sociohistorical context, including its African roots, Wake Up! shows how Hip Hop now embodies the worldview of growing numbers of youth and young adults in all churches. The book also examines the inherent religious themes embedded in Hip Hop music"--Cover p. [4].
Includes bibliographical references.
Electronic reproduction.
Keywords: African American youth -- Religious life; Hip-hop -- Religious aspects -- Christianity; Electronic books